From agricultural practices to mining activities: The consequences of this paradigm shift for the food security in Guinea - Diallo, Boubacar Sidi; Soumah , Mamadouba Sayon (Przegląd Prawa Rolnego, 2023)
This study aims to analyse the effects that the mining activity exercises on agriculture and the livelihoods of local communities in the Republic of Guinea. Mining and agricultural activities are intertwined in such a way that the operation of one affects the other. Over the years, mining activities have been seen to negatively affect farming, livestock grazing and fisheries in the surrounding communities. Mining consists in the excavation of useful and economically valuable minerals from deposits in the earth. Despite its potential to generate a large amount of revenue, the mining sector is not adequately regulated, and as a consequence creates a ground for illegal mining activities. These activities, depending on the type of mining, have a spectrum of effects on agricultural activities including competition for land control and use, pollution of water bodies and exposure of crops and livestock to the harmful effects of heavy metals. The cumulative effects of these activities have modified the agricultural practices, disrupted landscapes, and negatively influence the availability of food crops in the areas where mining activities are carried out, which in turn threatens the food security of the region of Boké. This article also evaluates the impacts of mining on agricultural activities in the region, with a view of providing evidence for policymakers for taking necessary action and foster sustainable solutions.